2020
DOI: 10.1093/mnras/staa2752
|View full text |Cite
|
Sign up to set email alerts
|

The GOGREEN survey: post-infall environmental quenching fails to predict the observed age difference between quiescent field and cluster galaxies at z > 1

Abstract: We study the star formation histories (SFHs) and mass-weighted ages of 331 UVJ-selected quiescent galaxies in 11 galaxy clusters and in the field at 1 < z < 1.5 from the Gemini Observations of Galaxies in Rich Early ENvironments (GOGREEN) survey. We determine the SFHs of individual galaxies by simultaneously fitting rest-frame optical spectroscopy and broadband photometry to stellar population models. We confirm that the SFHs are consistent with more massive galaxies having on average earlier for… Show more

Help me understand this report
View preprint versions

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

8
31
0

Year Published

2021
2021
2024
2024

Publication Types

Select...
8

Relationship

1
7

Authors

Journals

citations
Cited by 45 publications
(39 citation statements)
references
References 245 publications
(386 reference statements)
8
31
0
Order By: Relevance
“…Therefore, the age difference between Galaxy-D and the currently known PSB population ∼1.0 Gyr is one of the first known evidence of an ageenvironment relation at high z. Interestingly, a similar difference of 1 Gyr between clusters and field has also been found for local populations, where this relation has already been established (e.g., Bernardi et al 2006;Gallazzi et al 2021). Similar, but relatively tentative trends have also been detected at z ∼ 1.0-1.5 (Webb et al 2020). But unlike at low z, the age offset at z  3 is a sizable fraction of the stellar ages themselves, thereby manifesting as much more pronounced observational differences as has already been discussed in Section 5.1.…”
Section: Quiescence In a Dense Environmentsupporting
confidence: 60%
“…Therefore, the age difference between Galaxy-D and the currently known PSB population ∼1.0 Gyr is one of the first known evidence of an ageenvironment relation at high z. Interestingly, a similar difference of 1 Gyr between clusters and field has also been found for local populations, where this relation has already been established (e.g., Bernardi et al 2006;Gallazzi et al 2021). Similar, but relatively tentative trends have also been detected at z ∼ 1.0-1.5 (Webb et al 2020). But unlike at low z, the age offset at z  3 is a sizable fraction of the stellar ages themselves, thereby manifesting as much more pronounced observational differences as has already been discussed in Section 5.1.…”
Section: Quiescence In a Dense Environmentsupporting
confidence: 60%
“…Our finding that z 1.1 clusters are dynamically old appears to fit well in the scenario supported by the analyses of the cluster galaxy population based on GOGREEN survey data. These studies (Old et al 2020(Old et al , 2021Webb et al 2020) have in fact shown that the GOGREEN clusters are also old in terms of the age of their member galaxies.…”
Section: The Pseudo Phase-space Density Profilementioning
confidence: 98%
“…The high quenched fractions in 𝑧 1 clusters (Newman et al 2014;Cooke et al 2016;van der Burg et al 2020), with their implied short quenching timescales, have important consequences for the predicted stellar ages of the quiescent cluster galaxies. If the high quenched galaxy fraction is caused primarily by assembly bias -where galaxy formation started earlier in the protocluster compared to the field -then the stellar ages of the quiescent cluster galaxies at 𝑧 1 are predicted to be approximately a Gyr older than coeval field galaxies (van der Burg et al 2020;Webb et al 2020). On the other hand, if the high quiescent fraction was caused by rapid environmental quenching of infalling star-forming galaxies then the average stellar age of the quenched cluster galaxies is predicted to be 1.5 Gyrs younger than coeval quiescent field galaxies (Webb et al 2020), which quench over longer timescales.…”
Section: Introductionmentioning
confidence: 99%
“…It is the age dating studies of Gobat et al (2008); Rettura et al (2010); Lee-Brown et al (2017); Webb et al (2020) that causes a conundrum for mature high-redshift clusters, since these studies find z >1 cluster galaxies are only marginally older than field quiescent galaxies. The stellar age difference is not large enough to account for the excess of quenched galaxies through assembly bias, but environmental quenching cannot be the dominant quenching mechanism since the derived short environmental quenching timescales are in direct contradiction to the older stellar ages of the cluster quiescent galaxies.…”
Section: Introductionmentioning
confidence: 99%